PENERAPAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMA NEGERI 2 MUARA BELITI - Endang Lovisia (LP4MK STKIP PGRI Lubuklinggau, 2019)
This research purpose to determine the completeness of physics learning outcomes of class XI students of SMA Negeri 2 Muara Beliti after applying the experiment method. The problem in this study is that there are still many students who get grades below the Minimum Mastery Standard (KKM), which is 67. The type of method in this study uses an experimental method with pre-test and post-test one group design research conducted at SMAN 2 Muara Beliti. The population in this study were all students of class XI MIPA SMAN 2 Muara Beliti. The sample in this study was drawn randomly from a population of three classes, namely class XI MIPA 2, amounting to 30 students. Data collection techniques in this study were carried out through tests. The test result data were analyzed using the t test formula. Statistical test results obtained tcount = 8.544 ttable = 1.699 because tcount> ttable, thus indicating that the hypothesis Ho is rejected and Ha is accepted. While the average value in the pre-test 32.83 then in the post-test increased to 77.27. So it can be concluded that the average physics learning outcomes of students after applying the method of experiment is significantly complete.